Concatenating structural constraint effects at in for the sequential generation, stabilization, and transfer of acyclic aminocarbenes - Ruppert, Heiko; Meister, Arne; Pfretzschner, Ronja; Vieira, André Faria; Greb, Lutz (Journal of the American Chemical Society, 2024)
Structural constraint approaches have been employed toward different ends in recent years, from augmenting the nucleophilicity in pyramidalized low-valent p-block compounds to enhancing the Lewis acidities at planarized tetravalent p-block elements. While previous studies exploited these effects separately, this work introduces a strategy to concatenate structural constraint approaches at individual stages of a reaction sequence in a row to unlock a synthetic path unattainable by conventional methodologies. The boosted nucleophilicity resulting from the constrained tetracoordinated calix[4]pyrrolato stannate(II) dianion enables the reductive formation of sterically unprotected acyclic aminocarbenes. These amino carbenes are stabilized at the concomitantly formed square-planar stannane(IV) as air-stable adducts. Transfer of the carbenes onto copper(I) by cooperativity of the calix[4]pyrrole ligand finalizes this protocol to hitherto unreported yet prototypical carbene complexes. Detailed spectroscopic and quantum theoretical analyses establish the synergy of structural constraints and element-ligand cooperation as the linchpin to this reaction path and its selectivity.
Online veröffentlicht: 11. April 2024
Gesehen am 28.08.2024